STRIVING FOR QUALITY - THE ANSWER OF HISTORY (AN EXAMPLE OF HOSPITAL SECTOR) - Darina Mineva (Science & Research)

(untitled)
The aim of article is to examine the true role of the man-maker and the power that moves it to perfection. Presents the answer of the history. The historical path of quality development reveals the natural dependencies and factors: the relationship between manufacturers and the quality rules, the producer's acknowledged role of quality as a competitive advantage, the role of the production process, the internal motivation of the producer to create rules because of his dependence from other manufacturers and consumers. The two events: the division of labor and the division of labor alter the essence of motivation. The internal motivation of workers is diminishing, at the expense of the outside, as a material incentive. The internal motivation of the owners of the means of production increases with a motive for profit, at the expense of the external goal - the duty to society: paying taxes, improving the quality of life and securing salaries. The simultaneous possession of the means of production and the actual production of the product is a motivation for self-validation. In the separation of labor from capital and the shaping of the two classes of managerial possessing means of production and the people of direct labor, the motivation changes. He comes down to a base level in Maslow's pyramid - of survival and protection. In both groups there is a different occurrence - profit and salary. An example from a hospital is given. Three economic levers change the concept of quality: division of labor, separation of labor from capital and market exchange, which a priori leads to the idea that labor can be managed.